The effect of blind box product uncertainty on consumers’ purchase intention: The mediating role of perceived value and the moderating role of purchase intention - Zhang, Yi; Zhang, Tianqi (Frontiers in Psychology, 2022)
As the younger generation, who like to pursue novelty and excitement, becomes the main consumer and the traditional consumption culture changes in China, the blind box has become a popular product among young people with its uncertain characteristics. Previous studies have mainly explored the role of uncertainty in promotion, while this paper focuses on the role of uncertainty in daily sales of blind box products. Based on the stimulus–organism–response (SOR) theory, this paper conducted an online questionnaire survey and an empirical analysis in China, which examined the mechanism of the positive impact of uncertainty and the moderating effect of consumption purpose. The results show that uncertainty affects consumers’ purchase intention mainly through affecting their emotional value, which is one dimension of perceived value; consumer purpose also moderates the effect of uncertainty on perceived value, and the effect of perceived value on purchase intention. The results of this study are not only of great significance for understanding the uncertain marketing and blind box products, but also have management implications for enterprises to make use of the uncertain marketing.